2022
DOI: 10.1038/s43246-022-00318-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence of flat bands in breathing kagome semiconductor Nb3I8

Abstract: Kagome materials have become solid grounds to study the interplay among geometry, topology, correlation, and magnetism. Recently, niobium halide semiconductors Nb3X8 (X = Cl, Br, I) have been predicted to be two-dimensional magnets and these materials are also interesting for their breathing kagome geometry. However, experimental electronic structure studies of these promising materials are still lacking. Here, we report the spectroscopic evidence of flat and weakly dispersing bands in breathing-kagome semicon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The band gaps of Nb 3 Cl 8 and Nb 3 I 8 were experimentally reported to be 1.12 and ∼1 eV, respectively, , thereby indicating their potential in device applications. Additionally, Nb 3 Cl 8 and Nb 3 I 8 have been experimentally confirmed to possess topological flat bands. , …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The band gaps of Nb 3 Cl 8 and Nb 3 I 8 were experimentally reported to be 1.12 and ∼1 eV, respectively, , thereby indicating their potential in device applications. Additionally, Nb 3 Cl 8 and Nb 3 I 8 have been experimentally confirmed to possess topological flat bands. , …”
Section: Introductionmentioning
confidence: 98%
“…Additionally, Nb 3 Cl 8 and Nb 3 I 8 have been experimentally confirmed to possess topological flat bands. 18 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, FBs and Mott-like gap have been experimentally observed in Nb 3 X 8 . [39][40][41] The transition between band insulator and Mott insulator, as well as the molecular quantum spin liquid state, are theoretically predicted in Nb 3 X 8 . [42,43] These studies indicate that the flatness and topological properties of the FBs are predominated by electron hopping parameters and onsite energy of Nb sites in Nb 3 X 8 and Nb 3 QX 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nb 3 X 8 (X = Cl, Br, I) and Nb 3 QX 7 (Q = S, Se, Te; X = Cl, Br, I) possess 2D breathing-kagome lattice and weak van der Waals (vdW) interlayer interaction. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Their electronic bands in the close vicinity of the Fermi level are contributed by the metallic breathing-kagome layer, which is entirely composed of Nb atoms. These features make these materials appealing for exploring 2D FBs physics.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the layered Nb 3 I 8 has also been fabricated and studied. [23][24][25] Meanwhile, Dai et al theoretically demonstrated that the Nb 3 I 8 monolayer is a robust FM semiconductor with a moderate band gap, which exhibits the long-sought spontaneous valley polarization without requiring any external tuning. 26 Moreover, Ren et al proposed that the Ti 3 X 8 compounds with breathing kagome lattices are shown to form 2D intrinsic multiferroic semiconductors with the coexistence of ferroelectricity and ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%